An HuR mutant, HuR-V225I, identified in adult T-cell Leukemia/Lymphoma, alters the pro-apoptotic function of HuR - Bianca Colalillo; Sujitha Sali; Ali H. Aldouhki; Isabelle Aubry; Sergio Di Marco; Michel L. Tremblay; Imed E. Gallouzi (Cell Death Discovery)
Abstract The RNA-binding protein HuR regulates various cellular processes, such as proliferation, differentiation, and cell fate. Moreover, recent studies have shown that HuR modulates the expression of factors important for tumor growth and progression. Despite its prominent role in tumorigenesis, until recently, there have been no reported mutations in HuR that have been associated to cancer. Here, we show that a HuR mutation, HuR-V225I, previously identified in a patient with Adult T-cell Leukemia/Lymphoma, interferes with the pro-apoptotic function of HuR. In response to apoptosis, HuR translocates to the cytoplasm and is cleaved in a caspase-dependent manner. In cervical cancer cells, neuroblastoma cells, and T-lymphocytes, we observed a decrease in cleavage of the HuR-V225I mutant under apoptotic conditions. This effect was shown to be mediated by the nuclear retention of HuR-V225I. Finally, expression of the HuR-V225I mutant decreases the cell’s response to apoptotic stimuli through the increased expression of mRNAs encoding anti-apoptotic factors, such as XIAP and BCL-2. Therefore, our data establishes that the absence of HuR cytoplasmic translocation and cleavage promotes cell viability, and that acquiring this mutation during tumorigenesis may thus reduce the efficacy of cancer therapy.